Homogenisation of titanium - 6 aluminium - 4 vanadium (TI-6AL-4V) powder blends during sintering - Churu, Varaidzo Amanda (Department of Mechanical Engineering, 2023)
Titanium alloys have received significant attention in recent years primarily within the aerospace sector due to their superior material properties, high strength to weight ratios and high resistance to corrosion. However, high processing costs associated with the alloys have hindered their usage in other fields such as the automotive industry. The powder metallurgy (PM) method is an emerged method that may lower processing costs. The blended elemental (BE) route to produce titanium alloys has been identified as the cheapest process by which the PM process can be applied. The powder metallurgy method has a few limitations, one of the associated limitations is that elemental powder blends must be homogenized in terms of chemical composition for them to meet the same quality standards as ingot processed titanium alloys. To combine cost effectiveness with good mechanical property attainment, the sintering process should be optimized at the lowest temperatures and shortest duration. In the current study, Ti-6Al-4V alloys were synthesized by the blended elemental press and sinter powder metallurgy route. This was carried out using three different powder blends comprising of Ti (100µm) and TiH2 (63µm) as base powders, blended with either Al (75µm), V (25 µm) or a 60Al-40V (40µm) master alloy powder (MA). The powder blends made from the powders were namely TiH2 + MA, TiH2 + Al+ V and CpTi + MA. The average particle sizes in each case are indicated in parentheses. As a precursor to mechanical property measurement, the relative degree of homogenization that occurs during sintering of powders shaped by uniaxial pressing was investigated at sintering temperatures of 1000 - 1350⁰C under vacuum at times ranging from 0.5 hours to 4 hours. The homogenization was evaluated via scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDS) and X-ray diffraction (XRD). The density was measured using the Archimedes method. The EDS approach was used at a specific length scale (100µm× 100µm) to assess the degree of elemental mixing that occurs during the limited sintering exposure. A combination of SEM/EDS analysis and XRD was successfully used to measure homogenization progress of the powder blends. The different powder blends reached different levels of homogeneity at different temperature and time. The TiH2 + MA powder blend became fully homogeneous after sintering at 1350°C for 2 hours with a relative density of 98% ± 1. Three stable beta peaks coinciding with the wrought titanium spectra were also shown after sintering at 1350°C for 2 hours . The CpTi + MA powder did not reach full homogeneity as the TiH2 + MA powder blend at any of the sintering temperature and times but after sintering at 1350°C for 4 hours the samples demonstrated reasonable homogeneity, although still significantly less homogeneous than the wrought alloy. There were some peaks that had peak broadening and peak splitting also shown that were closely related to the beta peaks of the wrought titanium shown in the XRD spectra but were not fully stable and a relative density of 97% ±1. The TiH2 + Al + V powder blend also did not reach homogeneity at any of the sintering temperature and time, there was however an improvement in diffusivity of aluminium and vanadium after sintering at 1350°C for 4 hours, with a relative density of 96% ± 1, no beta peaks were shown in the XRD spectra. The factors that mainly affected homogeneity besides time and temperature were the type of base powder as well as alloying elements. From the experiments, it was noticed that when Al and V are added as elemental alloys there was a 2-hour increase in sintering time for relative homogeneity to improve due to aluminum diffusing faster than vanadium at lower temperatures and stabilizing the alpha titanium phase. Whereas when vanadium and aluminum were added as a master alloy it resulted in a faster diffusion of both elements, therefore, reaching homogeneity earlier. The combination of TiH2 + MA powder blend had the lowest temperature and time reaching homogeneity at 1350°C after 2 hours of sintering.